Simultaneous removal and optical determination of mercury ions by constructing fluorescent recombinant T. thermophila SB210 strains - Shu-Hui Zhao; Kai-Kang Hu; Jie Xiong; Jia-Wei Tu; Wei Miao (Ecotoxicology and Environmental Safety)
Removing and monitoring Hg2+ ions in the pollution sources based on microorganisms have the advantages of low cost and convenience. To reduce the harm of Hg2+ ions to humans and ecosystems in the environment, it is considered very meaningful to establish a biological treatment method using protozoa to simultaneously detect and remove Hg2+ ions in polluted water. In this work, the coding region of MTT1 and MTT5 genes in Tetrahymena thermophila SB210 (T. thermophila SB210) was replaced with green fluorescence protein (GFP) gene using genetic manipulation techniques. Fluorescent recombinant T. thermophila SB210 strains MTT1-GFP and MTT5-GFP were constructed, and the relationship between MTT1-GFP and MTT5-GFP and the effect of simultaneous response and removal of Hg2+ ions was explored. The knockout of MTT1 and MTT5 genes and introduction of GFP significantly reduced cell tolerance to Hg2+ ions, slightly increased the removal rate of Hg2+ ions, and induced fluorescence response to Hg2+ ions. Using MTT1-GFP at a cell density of 150 × 104 cells mL−1, the removal rate of Hg2+ ions were over 90 % at range 6000 μg L−1 to 10000 μg L−1 in 12 h. The limit of detection (LOD) was 1.063 μg L−1 and the linear detection range of Hg2+ concentration was 200–8000 μg L−1 using MTT1-GFP as fluorescence reporter. In addition, the different functional effects of MTT1-GFP and MTT5-GFP on Hg2+ and Cd2+ were compared. This study will expand our understanding of the role of MTT1 and MTT5 genes and provide a method for simultaneous response and removal of Hg2+ ions in water bodies using T. thermophila.